2021
DOI: 10.21203/rs.3.rs-490913/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Game-based education promotes sustainable water use

Abstract: In this study we estimate the impact of a game-based educational program aimed at promoting sustainable water usage among 2nd-4th grade students and their families living in the municipality of Lucca, Italy. To this purpose we exploited unique data from a quasi-experiment involving about two thousand students, one thousand participating (the treatment group) and one thousand not participating (the control group) in the program. Data were collected by means of a survey that we specifically designed and implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…If on the one hand the multimedia exhibit is finished, on the other hand, scientific research will not be closed yet. The project plans to collect behavioural data on cooperation trying to further expand and diversify the sample, following the example of other virtuous projects (Bilancini et al 2021), involving schools other than the initial ones. Unfortunately, Covid-19 has made it very difficult to collect data within a museum, but the end of the health emergency can help research, easing the imposed limitations and allowing the sample to be enlarged.…”
Section: Discussionmentioning
confidence: 99%
“…If on the one hand the multimedia exhibit is finished, on the other hand, scientific research will not be closed yet. The project plans to collect behavioural data on cooperation trying to further expand and diversify the sample, following the example of other virtuous projects (Bilancini et al 2021), involving schools other than the initial ones. Unfortunately, Covid-19 has made it very difficult to collect data within a museum, but the end of the health emergency can help research, easing the imposed limitations and allowing the sample to be enlarged.…”
Section: Discussionmentioning
confidence: 99%
“…The research protocol consists of a pre/post study implemented to measure sustainable behavior regarding water usage. Specifically, students' awareness about the efficient use of water was elicited using a questionnaire designed ad hoc by Bilancini et al (2023), which includes habits and sustainable behaviors related to water use (Appendix A.3 and A.4 report the original and the translated survey). The two surveys were collected just before the beginning of the program, in February 2019, and immediately after the end of the second phase, on May 2019.…”
Section: Research Protocolmentioning
confidence: 99%
“…The program was brought in several elementary schools of the city and relied on ludic engagement to teach students about the water cycle and to promote awareness about water waste and efficient water usage. In a previous study, Bilancini et al (2023) evaluated the effect of the educational program using a two-group design. Participants were assigned into a treatment group, for which the educational program was implemented, and a control group, composed of students not directly involved in the BLUTUBE program.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have confirmed that game-based learning can enhance public knowledge on social issues, change attitudes toward sustainable development and related subjects [18][19][20][21], increase motivation and facilitate different kinds of learning [16], and equip learners with the complex, cross-disciplinary concepts and knowledge necessary for the practice of sustainable development [22][23][24][25][26]. Based on its various advantages, game-based learning should be integrated into education [15] to deliver knowledge on comprehensive sustainable development to the public.…”
Section: Game-based Learningmentioning
confidence: 99%